Physio-biochemical responses of three sunflower (Helianthus annuus L.) lines to phosphate solubilizing bacteria and phosphorous-enriched biochar in saline soils - Jahanshahi, Siavash; Moaveni, Payam; Ghaffari, Mehdi; Mozafari, Hamid; Alizadeh, Bahram (Frontiers in Plant Physiology, 2024)
The usage of microbes and biochar (BC) is fundamental in decreasing the impacts of salinity stress by promoting plant growth and development. The purpose of this study was to determine the impact of phosphate solubilizing bacteria (PSB) and phosphorous (P)-enriched BC on the plant growth and biochemical characteristics for three lines of sunflower (Helianthus annuus L.) in saline soils. The study was designed with salinity at 100 mM NaCl and PSB (Bacillus subtilis) with 109 CFU and BC at 1500 Kg ha-1 in the sunflower lines including RGK38 (salt-sensitive), BGK35 (salt-moderately sensitive), and BGK259 (salt-tolerant) based on completely randomized block design (CRBD) in five replicates. Salinity considerably reduced grain yield, thousand grain weight (TGW), oil content, oil yield, chlorophyll (Chl) content, relative water content (RWC), K, and P, while enhancing malondialdehyde (MDA), electrolyte leakage (EL), Na+, and Cl- in all lines of sunflower with high rate in RGK38. The use of integrated PSB and BC contributed to increases in plant yield. In RGK38 exposed to salinity, PSB+BC raised grain yield (16%), oil yield (27%), RWC (14%), Chl a+b (24%), K (22%), P (127%), but lowered MDA (26%), Na+ (36%), and Cl- (41%). Heat map analysis revealed that RGK38 stood out significantly from the other two sunflower lines with the maximum variability under the treatments. MDA showed the most variability among the lines as an indicator of identifying the susceptibility to salinity, PSB, and BC. This study has encouraging implications for agricultural operations in stress-affected areas by highlighting the potential of combining PSB and BC as environmentally acceptable and sustainable ways to increase plant resilience in salty soils.